Usefulness of ß-D-glucan for diagnosis and follow-up of invasive candidiasis in onco-haematological patients. Issue 5 (May 2018) - Guitard, J.; Isnard, F.; Tabone, M.-D.; Antignac, M.; Brissot, E.; Senghor, Y.; Petit, A.; Leverger, G.; Hennequin, C.
Highlights: Evaluation of BDG to specifically diagnose invasive candidiasis in haematology. Both candidemia and chronic disseminated candidiasis (CDC) analysed. Sensitivity of BDG is low: 43.5% for candidemia, and 73% for CDC. BDG kinetics correlates to outcome of candidemia and CDC. In CDC, BDG negativation anticipates resolution of imaging lesions. Abstract: Objectives: Definitive diagnosis of invasive candidiasis (IC) may be difficult to achieve in patients with haematological malignancy (PHM). We aimed to evaluate the performance of BDG for the diagnosis and the follow-up of IC in PHM. Patients and methods: We retrospectively reviewed the serological data of BDG assay in adult and paediatric PHM, who developed candidemia or chronic disseminated candidiasis (CDC) through a 4-year period. Sensitivity and kinetics of BDG were determined for both clinical forms. Results: In a panel of 3027 PHM, incidence rates of candidemia and CDC ranged between 0.74 and 0.77 and 0.30 and 0.44 according to the group of patients. At the time of diagnosis, 43.5% and 73% of cases of candidemia and CDC had a positive BDG assay, respectively. We found a significant correlation between the level of BDG at diagnosis and the outcome of candidemia (p = 0.022). In all cases of CDC, BDG negative results were obtained 2 to 6 months before recovery of the CT-scan lesions. Conclusions: BDG exhibits a low sensitivity to detect IC in PHM, but its kinetics correlates the clinical outcome. Additional studies are warranted in patients with CDC to evaluate the interest of monitoring BDG levels to anticipate the discontinuation of antifungal maintenance therapy.